Measuring Carbon Emissions of Foreign Direct Investment in Host Economies - Borga, Maria (IMF Working Papers; Working Paper, 2022)
This paper presents estimates of the carbon emissions of FDI from capital formation funded by FDI and the production of foreign-controlled firms. The carbon intensity of capital formation financed by FDI has trended down, driven by reductions in the carbon intensity of electricity generation. Carbon emissions from the operations of foreign-controlled firms are greater than those from their capital formation. High emission intensities were accompanied by high export intensities in mining, transport, and manufacturing. Home country policies to incentivize firms to meet strict emissions standards in both their domestic and foreign operations could be important to reducing emissions globally.